A Parallel Processing and Synthesis Structure for Improving Access Security and Efficiency in SDN Environment. Issue 5 (1st September 2016) - Zhang, Peng; Chen, Xiangning; Ge, Yun; Jin, Lin
Abstract : After studying the routing and forwarding process of network stream and the implementation of SDN, we propose a retractable management model for flow table. A structure with parallel tables and synthesis processing is proposed according to the feature of SDN and traditional network. The parallel tables share the same storage resources. Thanks to the separation of data plane and control plane, control plane owns more computing resources than traditional device. It evaluates the role of nodes and the action of network flows, makes adjustment according to the historical and current information and streamlines flow tables by consolidating and simplifying old flow entries. Through simulation, it is proved that the realized method can defend offensive traffic while ensuring the safety of accessing and forwarding, especially existing blocking attack.